Asymmetry between the Knee Flexors in the Dominant Leg of Inter-university and College Handball Players: An Empirical Analysis: Investigating the Strength Disparities in Knee Flexors among Inter-university and College Handball Players (Journal of Advances and Scholarly Researches in Allied Education, 2022)
In the realm of handball, a fast-paced and physically taxing sport, the knee flexorsperformance, particularly in the dominant leg, plays a pivotal role in defining an athlete's agility andpower during match. This study researches deep into identifying and analysing the potential disparitiesin knee flexor strength between inter-university and college handball players, a segment that remainsunder-explored in existing literature. Through a well-structured experimental setup involving 30 malesubjects (15 from inter-university and 15 from college teams), this research utilizes the precision of theCSMI HUMAC NORM isokinetic dynamometer to measure the strength in torque (Nm) at a 60-degreeangle, post an adequate warm-up session, the study reveals significant strength differences between thetwo groups. The goal of this exploration is to shed light on the differences in physical conditioning andtraining methodologies between these two distinct cohorts. It aims to provide actionable insights anddata-backed suggestions to refine training regimens, particularly at the college level, to potentiallybridge the observed performance gap. Moreover, the findings of this research could pave the way for amore comprehensive understanding of the sport-specific physical conditioning demands and contributeto fostering an environment of competitive equity and enhanced performance in the field of handball.The statistical analysis employed a t-test to compare the means of the two groups at 0.05 level ofsignificance.